Design of localization course - Laucius, Rimgaudas; Dagienė, Valentina (Lietuvos matematikos rinkinys, 2005)
The paper deals with the design of localization courses for high education. In Lithuania, the localization of software is very important. Localization process is growing. We need a lot of high qualification translators. However, teaching of software localization is not a part of translators’ studies. All localizers are still volunteers. Curricula of localization are discussed in the paper.